Corporations as Corruption Offenders: Challenges and Solutions for Restorative Justice-Based Punishment - Kilikily, Nikolas Johan; Kristiawanto, Kristiawanto; Akkapin, Supaphorn (CV. Era Digital Nusantara, 2025)
The criminal prosecution of corporations involved in corruption in Indonesia has yet to demonstrate substantial effectiveness, both in terms of substantive justice and the enforcement of anti-corruption laws. Although corporations are legally recognized as subjects of criminal liability, enforcement practices remain limited, and sanctions imposed tend to be formalistic without triggering structural reforms within the company. This study employs a normative legal and comparative law approach to evaluate the effectiveness of existing regulations and to propose a more progressive model of corporate criminal liability. The findings indicate that corporate punishment should include preventive, restorative, and internal restructuring measures, rather than mere financial penalties. Therefore, regulatory reform and the application of multi-level sanctions are essential to establish deterrence and ensure sustainable justice in combating corporate corruption.